Common mode filter and manufacturing method thereof
By introducing a glass ceramic transition layer into the stacked common mode filter, the layering and warping problems arise after the ferrite and low dielectric ceramic materials are solved, and the stability and reliability of the product are improved.
Patent Information
- Application Number
- CN202411446406.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-11
AI Technical Summary
In the stacked common mode filter, the difference in thermal expansion curve between ferrite and low-dielectric ceramic materials leads to defects such as layering, interface warping, and large size differences after firing.
A transition layer made of glass ceramic material is added between the magnetic ferrite layer and the dielectric ceramic layer, through which the material composition is 70% to 90% silicate glass and 10% to 30% Al2O3 filler is passed The layer reduces the stress problem of the material.
The problems of layering, opening, warping, etc. between the interface between ferrite and low-dielectric ceramic materials have been improved, and the process stability and reliability of the product have been improved.
Smart Images

Figure CN119419034A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electronic components, and in particular to a common mode filter and a manufacturing method thereof. Background Art
[0002] Common mode filters can effectively suppress noise interference during signal transmission, so they are widely used in smart terminals. With the rapid development of the electronic information industry, electronic equipment continues to develop in the direction of miniaturization, lightweight, and high performance, and multilayer chip common mode filters have emerged. Their low cost and high performance have been favored by the global market.
[0003] One of the platforms of the laminated common mode filter is to use low dielectric ceramics and magnetic ferrite as the base material, lay electrodes on the low dielectric ceramic layer, and form a co-fired combination with electrical properties after multi-layer stacking and sintering. However, there is a large difference in the thermal expansion curves between ferrite materials and low dielectric ceramic materials, so when co-firing, the fired products will have defects such as delamination, interface warping, and large size differences. Therefore, how to solve the defects caused by material co-firing is the technical key of this platform. Summary of the invention
[0004] The first object of the present invention is to provide a common mode filter that can improve the problems of delamination, opening, warping, etc. occurring at the interface between ferrite and low dielectric ceramic material.
[0005] A second object of the present invention is to provide a method for manufacturing the common mode filter.
[0006] To achieve the first objective, the present invention provides a common mode filter, comprising a magnetic ferrite layer and a dielectric ceramic layer; the common mode filter further comprises a transition layer, the transition layer is located between the magnetic ferrite layer and the dielectric ceramic layer, the magnetic ferrite layer, the transition layer and the dielectric ceramic layer are stacked in sequence; the material of the transition layer is a glass ceramic material; in terms of weight percentage, the glass ceramic material comprises 70% to 90% of silicate glass, and the silicate glass comprises 80% to 90% of SiO 2 , 0 to 7% K 2 O and 5% to 17% Na 2 O.
[0007] It can be seen from the above scheme that due to the difference in sintering shrinkage temperature and shrinkage rate between the two substrates of the existing laminated common mode filter, the magnetic ferrite layer and the dielectric ceramic layer, there is a co-firing matching problem, which is easy to form delamination, opening and other problems. The common mode filter of the present invention adds a transition layer made of glass ceramic material between the magnetic ferrite layer and the dielectric ceramic layer, so that the material changes from a restricted shrinkage state to a relatively free shrinkage state, reduces stress problems, and improves the delamination, opening, warping and other problems between the ferrite and the low dielectric ceramic material interface. In addition, the transition layer material is a relatively pure silicate glass without other fillers as a skeleton. When the silicate glass content is low, the required melting point of the material is low, and a tangible transition layer cannot be formed; when the silicate glass content is too high, the material glass softening temperature point is high, the deformation ability is poor, and the effect of the stress transition layer cannot be achieved.
[0008] A preferred solution is that the glass ceramic material further includes a filler, and the filler is Al 2 O 3 , its content is 10% to 30%.
[0009] It can be seen that the appropriate content of Al 2 O 3 The filler can serve as a skeleton material to ensure the performance of the transition layer.
[0010] In a preferred embodiment, the material of the dielectric ceramic layer includes 80% to 85% borosilicate glass and 15% to 20% filler in weight percentage.
[0011] In a further embodiment, the filler includes at least one of aluminum oxide and zirconium oxide.
[0012] It can be seen that the filler can be aluminum oxide, zirconium oxide or a mixture of the two.
[0013] A further embodiment is that, in terms of weight percentage, the borosilicate glass comprises 75% to 90% SiO 2 , 0 to 5% Al 2 O 3 5% to 13% B 2 O 3 , 0 to 5% K 2 O and 1% to 6% Na 2 O.
[0014] A preferred solution is that the material of the magnetic ferrite layer includes (Ni 0.8 Zn 0.13 Cu 0.12 )Fe 1.95 O 4 and Bi 2 O 3 , and (N i0.8 Zn 0.13 Cu 0.12 )Fe 1.95 O 4 with Bi 2 O 3 The amount of substance ratio is 1:0.02.
[0015] A preferred solution is that the number of the dielectric ceramic layers is two. In the stacking direction, the two dielectric ceramic layers are respectively located on both sides of the magnetic ferrite layer, and a transition layer is provided between each dielectric ceramic layer and the magnetic ferrite layer.
[0016] It can be seen that any two adjacent dielectric ceramic layers and magnetic ferrite layers can be well bonded.
[0017] A preferred solution is that the number of magnetic ferrite layers is two. In the stacking direction, the two magnetic ferrite layers are respectively located on both sides of the dielectric ceramic layer, and a transition layer is provided between each magnetic ferrite layer and the dielectric ceramic layer.
[0018] A preferred solution is that the number of dielectric ceramic layers and the number of magnetic ferrite layers are both more than two layers, and the dielectric ceramic layers and the magnetic ferrite layers are arranged alternately in sequence along the stacking direction; a transition layer is provided between at least two adjacent dielectric ceramic layers and the magnetic ferrite layers; each transition layer is arranged symmetrically with the central plane as the center, and the central plane is parallel to the transition layer and passes through the midpoint of the common mode filter in the stacking direction.
[0019] It can be seen from this that a transition layer may be provided only between two adjacent dielectric ceramic layers and magnetic ferrite layers, and the two transition layers may be symmetrically arranged to ensure balanced force on the common mode filter.
[0020] To achieve the above-mentioned second purpose, the present invention provides a method for manufacturing the above-mentioned common mode filter, comprising: slurrying and casting the pretreated dielectric ceramic powder into a dielectric ceramic diaphragm, slurrying and casting the pretreated magnetic ferrite powder into a magnetic ferrite diaphragm, and slurrying and casting the pretreated glass ceramic powder into a glass ceramic diaphragm; stacking the magnetic ferrite diaphragm, the glass ceramic diaphragm and the dielectric ceramic diaphragm in sequence and then pressing them together. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a structural schematic diagram of the first structure of the common mode filter embodiment of the present invention.
[0022] Figure 2 It is a structural decomposition diagram of the first structure of the common mode filter embodiment of the present invention.
[0023] Figure 3 It is a structural schematic diagram of the second structure of the common mode filter embodiment of the present invention.
[0024] Figure 4 It is a structural schematic diagram of the third structure of the common mode filter embodiment of the present invention.
[0025] The present invention is further described below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION
[0026] See also Figure 1 and Figure 2 In this embodiment, the common mode filter of the first structure includes two magnetic ferrite layers, four transition layers and three dielectric ceramic layers. The dielectric ceramic layers and the magnetic ferrite layers are arranged alternately in sequence along the stacking direction, and a transition layer is provided between two adjacent dielectric ceramic layers and magnetic ferrite layers. Specifically, the two magnetic ferrite layers are the first magnetic ferrite layer 11 and the second magnetic ferrite layer 12, the four transition layers are the first transition layer 21, the second transition layer 22, the third transition layer 23 and the fourth transition layer 24, the three dielectric ceramic layers are the first dielectric ceramic layer 31, the second dielectric ceramic layer 32 and the third dielectric ceramic layer 33, the first dielectric ceramic layer 31, the first transition layer 21, the first magnetic ferrite layer 11, the second transition layer 22, the second dielectric ceramic layer 32, the third transition layer 23, the second magnetic ferrite layer 12, the fourth transition layer 24 and the third dielectric ceramic layer 33 are stacked in sequence.
[0027] See also Figure 3 The common mode filter of the second structure includes two magnetic ferrite layers, two transition layers and three dielectric ceramic layers. The dielectric ceramic layers and the magnetic ferrite layers are alternately arranged in sequence along the stacking direction, and the two transition layers are respectively located between the middle dielectric ceramic layer and the adjacent magnetic ferrite layer. Specifically, the two magnetic ferrite layers are the first magnetic ferrite layer 41 and the second magnetic ferrite layer 42, the two transition layers are the first transition layer 51 and the second transition layer 52, the three dielectric ceramic layers are the first dielectric ceramic layer 61, the second dielectric ceramic layer 62 and the third dielectric ceramic layer 63, and the first dielectric ceramic layer 61, the first magnetic ferrite layer 41, the first transition layer 51, the second dielectric ceramic layer 62, the second transition layer 52, the second magnetic ferrite layer 42 and the third dielectric ceramic layer 63 are stacked in sequence.
[0028] See also Figure 4The common mode filter of the third structure includes two magnetic ferrite layers, two transition layers and three dielectric ceramic layers. The dielectric ceramic layers and the magnetic ferrite layers are arranged alternately in sequence along the stacking direction. The two transition layers are respectively located between the dielectric ceramic layers on both sides and the adjacent magnetic ferrite layers. Specifically, the two magnetic ferrite layers are the first magnetic ferrite layer 71 and the second magnetic ferrite layer 72, the two transition layers are the first transition layer 81 and the second transition layer 82, the three dielectric ceramic layers are the first dielectric ceramic layer 91, the second dielectric ceramic layer 92 and the third dielectric ceramic layer 93, and the first dielectric ceramic layer 91, the first transition layer 81, the first magnetic ferrite layer 71, the second dielectric ceramic layer 92, the second magnetic ferrite layer 72, the second transition layer 82 and the third dielectric ceramic layer 93 are stacked in sequence.
[0029] In the common mode filters of the above three structures, the materials of each transition layer are glass ceramic materials. According to the weight percentage, the glass ceramic material includes 70% to 90% silicate glass and 10% to 30% filler, and the filler is Al 2 O 3 Among them, according to weight percentage, silicate glass includes 80% to 90% SiO 2 , 0 to 7% K 2 O and 5% to 17% Na 2 O.
[0030] The material of the dielectric ceramic layer is mainly composed of a borosilicate glass system, containing trace amounts of sodium and potassium elements, and adding aluminum oxide and zirconium oxide as skeleton fillers. In terms of weight percentage, the material of the dielectric ceramic layer includes 80% to 85% of borosilicate glass and 15% to 20% of fillers, and the fillers include aluminum oxide and zirconium oxide. Optionally, the filler can also be only aluminum oxide or zirconium oxide. In terms of weight percentage, the borosilicate glass includes 75% to 90% SiO 2 , 0 to 5% Al 2 O 3 5% to 13% B 2 O 3 , 0 to 5% K 2 O and 1% to 6% Na 2 O.
[0031] The materials of the magnetic ferrite layer include (Ni 0.8 Zn 0.13 Cu 0.12 )Fe 1.95 O 4 and Bi 2 O 3 , and (Ni 0.8 Zn 0.13 Cu 0.12 )Fe 1.95O 4 with Bi 2 O 3 The amount of substance ratio is 1:0.02.
[0032] In the following examples and comparative examples, the borosilicate glass in the dielectric ceramic layer contains SiO 2 The content of Al is 89.52%, 2 O 3 The content of B is 0.59%, 2 O 3 The content of Na 2 The content of O is 2.41%, K 2 The content of O is 0.39%. The filler of the dielectric ceramic layer contains Al 2 O 3 Accounting for 5.25% of the total weight of the material of the dielectric ceramic layer, ZrO 2 The total weight of the dielectric ceramic layer is 9.75%. The sintering temperature is 900°C, Na and K are fluxed in the glass, and the filler of the glass ceramic material is alumina.
[0033] First embodiment:
[0034] In this embodiment, the content of silicate glass in the glass ceramic material is 84.61%, Al 2 O 3 The content of filler is 15.39%. 2 The content of K is 86.58%, 2 The content of O is 0.47%, Na 2 The content of O is 12.95%. After testing, after the transition layer of this embodiment is used, there is no cracking problem in the transition layer area, and the defect ratio is 0%, that is, there is no defect.
[0035] Second embodiment:
[0036] In this embodiment, the content of silicate glass in the glass ceramic material is 85%, Al 2 O 3 The content of filler is 15%. 2 The content of K is 86.58%, 2 The content of O is 4.46%, Na 2 The content of O is 8.96%. After testing, after the transition layer of this embodiment is used, there is no cracking problem in the transition layer area, and the defect ratio is 0%.
[0037] Third embodiment:
[0038] In this embodiment, the content of silicate glass in the glass ceramic material is 90%, Al 2O 3 The content of filler is 10%. SiO in silicate glass 2 The content of K is 85.52%, 2 The content of O is 5.46%, Na 2 The content of O is 9.02%. After testing, after the transition layer of this embodiment is used, there is no cracking problem in the transition layer area, and the defect ratio is 0%.
[0039] The first comparison:
[0040] In this comparative example, the content of silicate glass in the glass ceramic material is 50%, Al 2 O 3 The content of filler is 50%. 2 The content of K is 84.26%, 2 The content of O is 3.80%, Na 2 The content of O is 11.94%. After testing, after the transition layer of this comparative example is used, the glass in the transition layer area melts and deforms seriously.
[0041] Second comparison:
[0042] In this comparative example, the content of silicate glass in the glass ceramic material is 95%, Al 2 O 3 The content of filler is 5%. SiO in silicate glass 2 The content is 90%, K 2 The content of O is 3.11%, Na 2 The content of O is 6.89%. After testing, after using the transition layer of this comparative example, cracking problems will occur in the middle area of the glass, and the defect ratio reaches 35%.
[0043] The materials of the above-mentioned embodiments and comparative examples are used to make a 0.8mm*0.6mm laminated common-mode filter, and the yellow light and laminated electronic device preparation process are used. Specifically, the manufacturing method of the common-mode filter includes: slurrying and casting the pretreated dielectric ceramic powder into a dielectric ceramic diaphragm, slurrying and casting the pretreated magnetic ferrite powder into a magnetic ferrite diaphragm, and slurrying and casting the pretreated glass ceramic powder into a glass ceramic diaphragm, the size of each diaphragm is 150mm*150mm, and the size of the magnetic ferrite diaphragm and the dielectric ceramic diaphragm is The thickness is 25μm. The three structures of magnetic ferrite diaphragm, glass ceramic diaphragm and dielectric ceramic diaphragm are stacked and pressed in sequence, that is, they are stacked in a symmetrical staggered manner. For example, for the common mode filter of the first structure, a glass ceramic diaphragm with a thickness of 15μm is added to each of the four dielectric ceramic-magnetic ferrite interfaces. After isostatic pressing, a Bar block with a thickness of 0.5mm is formed as a whole. The Bar block is cut into 1mm*0.75mm block green billets, and after debinding, it is sintered at 900℃ and then the performance is tested.
[0044] It can be seen from the above embodiments and comparative examples that when the content of silicate glass in the material of the transition layer is in the range of 70% to 90%, the transition layer can be used as a bonding and stress improvement layer to improve defects such as openings caused by stress mismatch at this location, thereby improving the process stability and reliability of the product. In addition, when the content of silicate glass in the material of the transition layer is less than 70%, due to the low content of silicate glass and the low melting point required for the material, a tangible transition layer cannot be formed, and the glass in the transition layer area melts and deforms severely. When the content of silicate glass in the material of the transition layer is greater than 90%, the content of silicate glass is too high, the softening temperature of the material glass is high, the deformation ability is poor, and the effect of the stress improvement layer cannot be achieved. The transition layer material is a relatively pure silicate glass. When the content of silicate glass is low, the melting point required for the material is low, and a tangible transition layer cannot be formed; when the content of silicate glass is too high, the softening temperature of the material glass is high, the deformation ability is poor, and the effect of the stress transition layer cannot be achieved.
[0045] In addition, in other embodiments, the number of magnetic ferrite layers can also be one, and the number of dielectric ceramic layers can be two. In the stacking direction, the two dielectric ceramic layers are respectively located on both sides of the magnetic ferrite layer, and a transition layer is arranged between each dielectric ceramic layer and the magnetic ferrite layer.
[0046] The number of dielectric ceramic layers can also be one, and the number of magnetic ferrite layers can be two. In the stacking direction, the two magnetic ferrite layers are respectively located on both sides of the dielectric ceramic layer, and a transition layer is provided between each magnetic ferrite layer and the dielectric ceramic layer.
[0047] The number of magnetic ferrite layers and the number of dielectric ceramic layers can also be more than two layers, and the specific number can be changed as needed. The above changes can also achieve the purpose of the present invention.
[0048] Finally, it should be emphasized that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. Common mode filter, including a magnetic ferrite layer and a dielectric ceramic layer; Features: The common mode filter further comprises a transition layer, wherein the transition layer is located between the magnetic ferrite layer and the dielectric ceramic layer, and the magnetic ferrite layer, the transition layer and the dielectric ceramic layer are stacked in sequence; The material of the transition layer is glass ceramic material; In terms of weight percentage, the glass ceramic material includes 70% to 90% silicate glass, and the silicate glass includes 80% to 90% SiO2, 0% to 7% K2O and 5% to 17% Na2O.
2. The common mode filter according to claim 1, characterized in that: The glass ceramic material further comprises a filler, which is Al2O3, and the content of the filler is 10% to 30%.
3. The common mode filter according to claim 1, characterized in that: In terms of weight percentage, the material of the dielectric ceramic layer includes 80% to 85% of borosilicate glass and 15% to 20% of filler.
4. The common mode filter according to claim 3, characterized in that: The filler includes at least one of aluminum oxide and zirconium oxide.
5. The common mode filter according to claim 3, characterized in that: In terms of weight percentage, the borosilicate glass includes 75% to 90% SiO2, 0% to 5% Al2O3, 5% to 13% B2O3, 0% to 5% K2O and 1% to 6% Na2O.
6. The common mode filter according to any one of claims 1 to 5, characterized in that: The material of the magnetic ferrite layer includes (Ni 0.8 Zn 0.13 Cu 0.12 )Fe 1.95 O4 and Bi2O3, and (Ni 0.8 Zn 0.13 Cu 0.12 )Fe 1.95 The molar ratio of O4 to Bi2O3 is 1:0.
02.
7. The common mode filter according to any one of claims 1 to 5, characterized in that: There are two dielectric ceramic layers. In the stacking direction, the two dielectric ceramic layers are respectively located on both sides of the magnetic ferrite layer. The transition layer is arranged between each dielectric ceramic layer and the magnetic ferrite layer.
8. The common mode filter according to any one of claims 1 to 5, characterized in that: The number of the magnetic ferrite layers is two. In the stacking direction, the two magnetic ferrite layers are respectively located on both sides of the dielectric ceramic layer. The transition layer is arranged between each magnetic ferrite layer and the dielectric ceramic layer.
9. The common mode filter according to any one of claims 1 to 5, characterized in that: The number of the dielectric ceramic layers and the number of the magnetic ferrite layers are both more than two layers, and the dielectric ceramic layers and the magnetic ferrite layers are alternately arranged in sequence along the stacking direction; The transition layer is disposed between at least two adjacent dielectric ceramic layers and the magnetic ferrite layers; The transition layers are symmetrically arranged with the central plane as the center. The central plane is parallel to the transition layers and passes through the midpoint of the common mode filter in the stacking direction.
10. A method for manufacturing a common mode filter, for manufacturing the common mode filter according to any one of claims 1 to 9, the manufacturing method comprising: The pre-treated dielectric ceramic powder is slurried and cast into a dielectric ceramic diaphragm, the pre-treated magnetic ferrite powder is slurried and cast into a magnetic ferrite diaphragm, and the pre-treated glass ceramic powder is slurried and cast into a glass ceramic diaphragm; The magnetic ferrite diaphragm, the glass ceramic diaphragm and the dielectric ceramic diaphragm are stacked in sequence and then pressed together.